A high and low temperature resistant modified PBS material, a preparation method and use thereof

CN122685866APending Publication Date: 2026-09-04SHANDONG DAWN DEGRADABLE MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610518840.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-20
Publication Date
2026-09-04

AI Technical Summary

Technical Problem

[0009]本发明针对现有PBS改性技术中高低温性能无法协同提升、易损失生物降解性和相容性的技术缺陷,提供一种耐高低温改性PBS材料及其制备方法

Benefits of technology

(1)本发明的改性PBS材料高低温性能协同提升,温度适应范围广泛。本发明通过化学键合对PBS引入刚性环状结构和柔性聚醚链段的协同改性,实现了PBS高低温性能的同步提升。降冰片烯二甲醇-丁二酸预聚体的刚性双环笼状结构嵌入PBS分子链后,通过空间位阻效应阻碍分子链的热运动,使材料的热变形温度提升至130℃以上,耐高温热降解和热变形能力显著增强;数均分子量500~2000g/mol的聚乙二醇柔性链段接枝到PBS分子链上,降低了分子链的结晶度,提升了分子链的低温柔韧性,使材料在-20℃时的简支梁冲击强度保持在15kJ/m²以上。改性后材料能在-20℃至130℃范围内保持稳定的力学性能,突破了传统改性技术难以兼顾高低温性能的瓶颈。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application provides a high and low temperature resistant modified PBS material, a preparation method and an application. The modified PBS comprises the following raw materials in parts by weight: succinic acid: 100 parts; 1,4-butanediol: 110-130 parts; norbornene dimethylol succinic acid prepolymer: 15-30 parts; polyethylene glycol: 5-15 parts; a catalyst: 0.05-0.2 parts; an antioxidant: 0.1-0.5 parts; wherein the number average molecular weight of the norbornene dimethylol succinic acid prepolymer is 1000-2000 g / mol; and the number average molecular weight of the polyethylene glycol is 500-2000 g / mol. By introducing rigid norbornene bicyclic structure and flexible polyethylene glycol segments through chemical bonding, the high and low temperature performance of the PBS is synergistically improved, the modified PBS material can maintain stable mechanical properties in the range of-20 DEG C to 130 DEG C, meanwhile, the modified PBS material has excellent biodegradability, compatibility and processing performance, and the preparation process is simple and controllable, and is suitable for industrial large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biodegradable polymer materials technology, specifically to a high and low temperature resistant modified PBS material, its preparation method, and its uses. Background Technology

[0002] Polybutylene succinate (PBS) is a typical aliphatic polyester biodegradable material with excellent biodegradability, good mechanical properties, and processing performance. It has already achieved large-scale application in civilian fields such as packaging materials, agricultural mulch films, and disposable tableware. With the deepening implementation of the global "plastic ban" and the upgrading and development of the environmental protection industry, the application scenarios of PBS are expanding from normal temperature environments to extreme temperature environments, such as cold chain logistics packaging (requiring tolerance to temperatures below -20°C), automotive interior parts (requiring tolerance to temperatures above 100°C), and outdoor biodegradable products (requiring high and low temperature cycling).

[0003] However, pure PBS has significant temperature performance defects, which has become the core bottleneck for its expansion into extreme temperature application scenarios: poor low temperature resistance. When the temperature is below -10℃, the crystallinity of the material molecular chain increases and the toughness decreases sharply, making it prone to brittleness and unable to meet the low temperature toughness requirements of cold chain transportation for packaging materials; insufficient high temperature resistance. When the temperature is above 120℃, the material is prone to thermal degradation and thermal deformation, resulting in reduced mechanical strength and yellowing appearance, which limits its application in medium and high temperature scenarios such as automotive interiors.

[0004] To improve the temperature adaptability of PBS, existing technologies mainly employ two methods: physical blending and chemical modification. However, both methods have insurmountable technical drawbacks, failing to achieve synergistic improvement in high and low temperature performance and easily compromising the inherent biodegradability of PBS.

[0005] Physical blending: Blending PBS with flexible polymers (such as PBAT) or rigid fillers (such as talc and glass fiber) can only improve low-temperature or high-temperature resistance individually. However, it suffers from poor component compatibility, significant phase separation, and uneven mechanical properties. Long-term use can also lead to component migration, resulting in material performance degradation. For example, CN 115386199 B discloses a high-temperature resistant, food-contact, fully biodegradable PBS alloy material, which, by weight, contains: 40-80 parts of low-precipitation PBS masterbatch, 10-30 parts of PLA, 5-10 parts of talc, 0.5-2 parts of anti-hydrolysis agent, 0.2-0.5 parts of chain extender, and 0.2-0.5 parts of lubricant. While the addition of PLA, talc, and anti-hydrolysis agent improves heat resistance, it does not improve low-temperature resistance, and the component migration problem caused by physical blending reduces the long-term stability of the material.

[0006] Chemical copolymerization: This method involves random copolymerization by introducing comonomers. Introducing flexible monomers (such as adipic acid) can improve low-temperature toughness but further reduces high-temperature resistance. Introducing rigid aromatic monomers can improve heat resistance but significantly reduces the biodegradability of the material. Furthermore, the temperature adaptability of the modified material remains limited, failing to cover the extreme temperature range of -20℃ to 130℃. For example, CN 118685006 A discloses a heat-resistant PBS-based copolyester, obtained by blending polybutylene succinate-based copolyester and layered bimetallic hydroxide. The polybutylene succinate-based copolyester is obtained by copolymerization of a first monomer, a second monomer, and a third monomer. The first monomer is 1,4-butanediol; the second monomer is succinic acid and / or dialkyl succinate; and the third monomer is selected from one or more of diols, diacids, and corresponding esters having aromatic rings, alicyclic rings, or heterocyclic rings. This technology improves heat resistance by introducing aromatic diacids as the third monomer but does not solve the low-temperature resistance problem, and the introduction of aromatic structures reduces the material degradation rate. For example, CN 115926123 A discloses a copolymerization modification of polybutylene adipate (PBS) and its preparation method. The raw materials are 1,4-succinic acid, 1,4-butanediol, tetrabutyl titanate, and PBS diol. The polyester diol is synthesized using a high-temperature nitrogen method. Adipic acid and 1,4-butanediol are weighed at an acid / alcohol molar ratio of 1:1.3 and subjected to esterification. Different amounts of PBS diol are added during the esterification reaction. The esterified product and tetrabutyl titanate are added to a polycondensation reactor, the polycondensation reaction is controlled, and a vacuum is applied. This technology, through copolymerization modification of PBS with PBS diol, only improves flexibility and low-temperature toughness, while further deteriorating high-temperature resistance.

[0007] Composite modification method: In-situ polymerization modification using fillers such as inorganic whiskers can simultaneously improve some thermal and mechanical properties, but the temperature adaptability range of the modified material is still narrow, and the cross-linking reaction easily leads to excessively high melt viscosity, resulting in decreased processing performance and hindering large-scale application. For example, CN102558793 A discloses a PBS / basic magnesium sulfate whisker composite material, with the following raw material composition: 70-99 parts PBS, 0.5-15 parts epoxy chain extender, 0.5-20 parts modifier, 0.01-1 part antioxidant, and 0.0001-0.01 parts accelerator, totaling 100 parts by weight. The above-mentioned parts by weight of PBS, modifier, and epoxy chain extender are placed in a vacuum oven for drying. The dried PBS, modifier, chain extender, and antioxidant are mixed in a high-speed mixer. Finally, the mixture is melt-blended in a single-screw extruder to obtain high melt strength PBS. However, the material's heat distortion temperature can only be increased to a limited extent, and the three-dimensional network structure formed by epoxy cross-linking narrows the material's processing window, thus limiting its application scenarios.

[0008] In summary, existing modification technologies cannot simultaneously solve the core problem of poor high and low temperature resistance of PBS, and are prone to problems such as loss of compatibility, processability, and biodegradability, which have become urgent technical challenges to be solved in the current upgrade of PBS materials. Summary of the Invention

[0009] This invention addresses the shortcomings of existing PBS modification technologies, such as the inability to synergistically improve high and low temperature performance and the easy loss of biodegradability and compatibility. It provides a high- and low-temperature resistant modified PBS material and its preparation method. This invention achieves a synergistic improvement in the high and low temperature performance of PBS by chemically bonding a rigid norbornene bicyclic structure with flexible polyethylene glycol segments. The modified PBS material maintains stable mechanical properties within a temperature range of -20℃ to 130℃, while also exhibiting excellent biodegradability, compatibility, and processability. Furthermore, the preparation process is simple and controllable, making it suitable for large-scale industrial production.

[0010] The technical solution of the present invention is as follows: A high and low temperature resistant modified PBS material, comprising the following raw materials in parts by weight: Succinic acid: 100 parts; 1,4-Butanediol: 110~130 parts; Norbornenedimethyl-succinic acid prepolymer: 15-30 parts; Polyethylene glycol: 5-15 parts; Catalyst: 0.05~0.2 parts; Antioxidant: 0.1~0.5 parts; The number-average molecular weight of the norbornene dimethyl succinic acid prepolymer is 1000~2000 g / mol. The number-average molecular weight of the polyethylene glycol is 500~2000 g / mol.

[0011] Furthermore, the tensile strength of the high and low temperature resistant modified PBS material is 30~40MPa, and the elongation at break is 300~360%.

[0012] Furthermore, the heat distortion temperature of the high and low temperature resistant modified PBS material is 130~140℃.

[0013] Furthermore, the biodegradation rate of the high and low temperature resistant modified PBS material is 91-95% after 6 months.

[0014] Furthermore, the impact strength of the modified PBS material resistant to high and low temperatures at -20℃ is 15~20kJ / m².

[0015] Further, the preparation method of the norbornene dimethylol-succinic acid prepolymer is as follows: norbornene dimethylol (bicyclo[2.2.1]heptane-2,3-dimethylol) and succinic acid are added to a reaction vessel at a molar ratio of 1:(1.05~1.1), and the reaction is carried out at a constant temperature of 140~160℃ for 2~3h under a nitrogen atmosphere, and then the temperature is lowered to 80~100℃ to obtain the prepolymer.

[0016] Furthermore, the norbornenedimethylethanol-succinic acid prepolymer contains a rigid bicyclic cage-like cyclic aliphatic structure that can be chemically bonded into the PBS molecular chain.

[0017] Furthermore, the polyethylene glycol is a linear aliphatic polyether with hydroxyl end groups, which can undergo esterification reactions with succinic acid and 1,4-butanediol, and be grafted onto the PBS molecular chain to form flexible segments.

[0018] Furthermore, the catalyst is a composite system of tetrabutyl titanate and lipase with a mass ratio of 1:(0.3~0.5); or a composite system of tetraisopropyl titanate with a mass ratio of 1:(0.3~0.5).

[0019] Furthermore, the lipase is selected from one or more of thermophilic lipase, lipase Novozym 435, porcine pancreatic lipase, and Candida rugosa lipase; the enzyme activity of the lipase is ≥10000U / g.

[0020] Furthermore, the antioxidant is a compound of hindered phenolic antioxidants and phosphite antioxidants.

[0021] More preferably, the antioxidant comprises a compound of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (antioxidant 1010) or octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1076) and tris[2,4-di-tert-butylphenyl] phosphite (antioxidant 168), wherein the mass ratio of the two is 1:(1~2).

[0022] The present invention also provides a method for preparing the aforementioned high and low temperature resistant modified PBS material, comprising the following steps: Step 1: Esterification reaction Succinic acid, 1,4-butanediol, norbornenedimethyl-succinic acid prepolymer, polyethylene glycol and some catalyst are added to a reactor and esterification reaction is carried out under an inert atmosphere until the water output reaches more than 90% of the theoretical output. Step 2: Polycondensation reaction Add the remaining catalyst and antioxidant to the above esterification reaction system to carry out a polycondensation reaction; Step 3: Extrusion Granulation After terminating the polycondensation reaction, nitrogen gas is introduced to break the vacuum, and the molten material in the reaction system is extruded under pressure and granulated. After vacuum drying, a high and low temperature resistant modified PBS material is obtained.

[0023] Furthermore, in step 1, the temperature of the esterification reaction is 160~180℃.

[0024] Furthermore, in step 1, the esterification reaction takes 2 to 4 hours.

[0025] Furthermore, in step 1, the stirring rate of the esterification reaction is 100~200 r / min.

[0026] More preferably, in step 1, succinic acid, 1,4-butanediol, norbornenedimethyl-succinic acid prepolymer, polyethylene glycol and 50 wt% catalyst are added to an atmospheric pressure polymerization reactor equipped with a distillation and water separation device, and then the reactor is sealed and purged with nitrogen 3 to 5 times.

[0027] More preferably, in step 1, the reactor is heated to 160~180℃ under nitrogen protection and the esterification reaction is carried out at a stirring rate of 100~200 r / min for 2~4 h. The water generated in the reaction is separated in real time by a distillation device until the water output reaches more than 90% of the theoretical output, thus completing the esterification reaction.

[0028] Furthermore, in step 2, after adding catalyst and antioxidant, the reaction system is heated to 210~230℃, while gradually evacuating to a vacuum degree ≤100Pa.

[0029] More preferably, in step 2, the remaining 50 wt% catalyst and antioxidant are added to the esterification reaction system, the reactor is heated to 210~230℃, and at the same time, the system vacuum is gradually reduced to ≤100 Pa by step-by-step vacuuming.

[0030] Furthermore, in step 2, the polycondensation reaction is carried out at a stirring rate of 50~100 r / min.

[0031] Furthermore, in step 2, the polycondensation reaction takes 3 to 6 hours.

[0032] More preferably, in step 2, the vacuum polycondensation reaction is carried out at a stirring rate of 50~100 r / min for 3~6 h until the system reaches the target melt viscosity, for example, melt index 3-5, and then the polycondensation is stopped.

[0033] Furthermore, in step 3, after the polycondensation is completed, heating is stopped, nitrogen gas is introduced into the reactor to break the vacuum and the pressure is increased to 0.1~0.3 MPa.

[0034] Further, in step 3, the molten material in the reactor is conveyed to a single-screw / twin-screw extruder through a bottom melt valve, impurities and gel particles are removed by filtration, and the material is melt-extruded at an extrusion temperature of 170~190℃. The material is then processed into uniform particles (particle size 2~5mm) by water-cooled stringing and rotary pelletizing.

[0035] Furthermore, in step 3, the water cooling temperature is 20~40℃; the pelletizing speed is 200~500 r / min.

[0036] Further, in step 3, the obtained wet particles are sent to a vacuum drying oven or a continuous vacuum dryer and vacuum dried at 60~80℃ and vacuum degree ≤-0.08 MPa for 8~12 h until the particle moisture content is ≤0.05 wt%, thus obtaining high and low temperature resistant modified PBS material.

[0037] The present invention also provides an article obtained by molding the high and low temperature resistant modified PBS material, the article being a cold chain packaging box, automotive interior parts, outdoor biodegradable tableware, or garden mulch.

[0038] The beneficial effects of this invention are as follows: (1) The modified PBS material of this invention exhibits synergistic improvement in high and low temperature performance and a wide temperature adaptability range. This invention achieves simultaneous improvement in the high and low temperature performance of PBS by introducing a rigid cyclic structure and flexible polyether segments into PBS through chemical bonding. After the rigid bicyclic cage structure of norbornenedimethyl-succinic acid prepolymer is embedded into the PBS molecular chain, the thermal motion of the molecular chain is hindered by the steric hindrance effect, which raises the heat distortion temperature of the material to above 130℃, significantly enhancing its resistance to high-temperature thermal degradation and heat distortion. Flexible polyethylene glycol segments with a number average molecular weight of 500~2000 g / mol are grafted onto the PBS molecular chain, reducing the crystallinity of the molecular chain and improving its low-temperature flexibility, so that the simply supported beam impact strength of the material at -20℃ remains above 15 kJ / m². The modified material can maintain stable mechanical properties in the range of -20℃ to 130℃, breaking through the bottleneck of traditional modification technology that is difficult to balance high and low temperature performance.

[0039] (2) The modified PBS material of the present invention exhibits excellent compatibility and stable mechanical properties. The modified components of the present invention are all chemically bonded to the PBS backbone, rather than physically blended: the ester structure of the norbornene diallyl-succinic acid prepolymer is highly compatible with the PBS backbone, and the hydroxyl end groups of polyethylene glycol undergo esterification with the PBS backbone to form covalent bonds, fundamentally avoiding the phase separation and component migration problems commonly encountered in physical blending. The modified material has a tensile strength ≥30MPa and an elongation at break ≥300%, exhibiting superior mechanical properties compared to pure PBS and traditional blended modified materials, with no significant performance degradation during long-term use.

[0040] (3) The modified PBS material of the present invention exhibits excellent biodegradability and meets environmental protection standards. The raw materials selected in the present invention are all biodegradable aliphatic components. The cyclic structure of norbornenedimethylethanol-succinic acid prepolymer is connected to the PBS backbone through ester bonds, and polyethylene glycol is a linear aliphatic polyether. Neither of these components affects the degradation of ester groups in the PBS molecular chain by microorganisms. The modified material exhibits a biodegradability rate of ≥90% in a natural soil environment after 6 months, meeting the biodegradability performance standard of GB / T 19277.1-2011 "Determination of the final aerobic biodegradability of materials under controlled composting conditions by measuring the released carbon dioxide - Part 1: General method", thus achieving the dual goals of "improved high and low temperature performance" and "maintained biodegradability".

[0041] (4) The modified PBS material of the present invention has a simple and controllable preparation process, which is suitable for industrial production. The present invention adopts a one-step esterification-condensation continuous process, which does not require complex special equipment, and the reaction conditions are mild and easy to control; the composite catalyst combines the high catalytic activity of tetrabutyl titanate and the high selectivity of lipase, which can accelerate the esterification and condensation reaction process, shorten the reaction cycle, reduce the generation of by-products, and reduce the metal residue (≤50ppm), so that the material can be used in high-end scenarios such as food contact grade cold chain packaging.

[0042] (5) The modified PBS material of the present invention has good processing performance and a wide range of applications. The modified PBS material of the present invention has moderate melt viscosity and a wide processing window. It can be made into films, sheets, injection molded parts, foam products, etc. through conventional polymer processing technologies such as blown film, injection molding, extrusion, and vacuum forming. It is widely used in cold chain packaging films, fresh food preservation boxes, automotive interior panels, outdoor biodegradable tableware, garden mulch films and other fields, and has good industrialization prospects. Detailed Implementation

[0043] Preferred embodiments of the invention will now be described in more detail. While preferred embodiments of the invention are described below, it should be understood that the invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided so that the invention will be thorough and complete, and will fully convey the scope of the invention to those skilled in the art.

[0044] Example 1 A high and low temperature resistant modified PBS material, comprising the following raw materials in parts by weight: Succinic acid: 100 parts; 1,4-Butanediol: 110 parts; Norbornenedimethyl-succinic acid prepolymer: 15 parts; Polyethylene glycol: 5 parts; Catalyst: 0.05 parts; Antioxidant: 0.1 parts; The number-average molecular weight of the norbornene dimethyl succinic acid prepolymer is 1000 g / mol. The number average molecular weight of polyethylene glycol is 500~2000 g / mol; The tensile strength of the high and low temperature resistant modified PBS material is 30.3 MPa, and the elongation at break is 306%. The heat distortion temperature of the high and low temperature resistant modified PBS material is 130℃; The biodegradation rate of the high and low temperature resistant modified PBS material was 91% after 6 months. The impact strength of the high and low temperature resistant modified PBS material at -20℃ is 15.4 kJ / m².

[0045] The preparation method is as follows: 1. Preparation of prepolymer: norbornenediethanol and succinic acid were added to a reaction vessel at a molar ratio of 1:1.05 and reacted at 140℃ for 3 h under a nitrogen atmosphere. Then the temperature was lowered to 80~100℃ to obtain a norbornenediethanol-succinic acid prepolymer with a number average molecular weight of 1000 g / mol. 2. Raw material ratio: 100g succinic acid, 110g butanediol, 15g prepolymer, 5g polyethylene glycol, 0.05g catalyst, 0.1g antioxidant; 3. The preparation method is as follows: Step 1: Esterification reaction Succinic acid, butanediol, prepolymer, polyethylene glycol, and 0.025g of catalyst (a composite system of tetrabutyl titanate and lipase Novozym 435 in a mass ratio of 1:0.3) were added to the reactor. The reactor was purged with nitrogen three times, and the temperature was raised to 160℃ under nitrogen protection. The esterification reaction was carried out at a stirring rate of 100 r / min for 4 hours. The water generated in the reaction was separated in real time by a distillation device until the water output reached the theoretical value of 92%, thus completing the esterification reaction. Step 2: Polycondensation reaction Add the remaining 0.025g of catalyst and antioxidant (a mixture of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1010) and tris[2,4-di-tert-butylphenyl]phosphite (antioxidant 168) in a mass ratio of 1:2) to the above esterification reaction system. Heat the reaction system to 210℃ and simultaneously apply vacuum in a stepwise manner, gradually reducing the vacuum degree of the system to 100Pa. Perform vacuum polycondensation reaction at a stirring rate of 50r / min for 6h until the system reaches the target melt viscosity, such as melt index 3-5, and then stop the polycondensation. Step 3: Extrusion Granulation After the polycondensation is complete, heating is stopped, nitrogen gas is introduced into the reactor to break the vacuum and the pressure is increased to 0.1 MPa; The molten material in the reactor is conveyed to the twin-screw extruder through the bottom melt valve. Impurities and gel particles are removed by the filter screen. The material is melt-extruded at an extrusion temperature of 170°C and produced into uniform particles with a particle size of 2~5mm by water-cooled stringing and rotary pelletizing. The water cooling temperature is 20℃; the pelletizing speed is 200 r / min. Subsequently, the obtained wet particles were sent to a vacuum drying oven and vacuum dried for 8 h at 60℃ and a vacuum degree ≤ -0.08 MPa until the particle moisture content was ≤ 0.05 wt%, thus obtaining high and low temperature resistant modified PBS material.

[0046] Example 2 A high and low temperature resistant modified PBS material, comprising the following raw materials in parts by weight: Succinic acid: 100 parts; 1,4-Butanediol: 120 parts; Norbornenedimethyl-succinic acid prepolymer: 22 parts; Polyethylene glycol: 10 parts; Catalyst: 0.12 parts; Antioxidant: 0.3 parts; Among them, the number-average molecular weight of norbornenedimethyl-succinic acid prepolymer is 1500 g / mol; The number average molecular weight of polyethylene glycol is 500~2000 g / mol; The tensile strength of the high and low temperature resistant modified PBS material is 32.6 MPa, and the elongation at break is 340%. The heat distortion temperature of the high and low temperature resistant modified PBS material is 134℃; The biodegradability of the high and low temperature resistant modified PBS material is 93% after 6 months; The impact strength of the high and low temperature resistant modified PBS material at -20℃ is 18.6 kJ / m².

[0047] The preparation method is as follows: 1. Preparation of prepolymer: Norbornene dimethyl alcohol and succinic acid were added to a reaction vessel at a molar ratio of 1:1.1 and reacted at 150°C for 2.5 h under a nitrogen atmosphere. The temperature was then lowered to 80-100°C to obtain a prepolymer with a number average molecular weight of 1500 g / mol. 2. Raw material ratio: 100g succinic acid, 120g butanediol, 22g prepolymer, 10g polyethylene glycol, 0.12g catalyst, 0.3g antioxidant; 3. The preparation method is as follows: Step 1: Esterification reaction All raw materials and 0.06g of catalyst (a composite system of tetrabutyl titanate and lipase Novozym 435 in a mass ratio of 1:0.3) were added to the reactor. The reactor was purged with nitrogen three times. Under nitrogen protection, the temperature was raised to 170℃ and the esterification reaction was carried out at a stirring rate of 150 r / min for 3 hours. The water generated in the reaction was separated in real time by a distillation device until the water output reached 95% of the theoretical value, thus completing the esterification reaction. Step 2: Polycondensation reaction The remaining catalyst and antioxidant (a mixture of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1010) and tris[2,4-di-tert-butylphenyl]phosphite (antioxidant 168) in a mass ratio of 1:2) were added to the above esterification reaction system. The reaction system was heated to 220°C, and a vacuum was drawn in stages to gradually reduce the vacuum degree of the system to 50 Pa. The vacuum polycondensation reaction was carried out at a stirring rate of 80 r / min for 4.5 h until the system reached the target melt viscosity, such as melt index 3-5, and the polycondensation was stopped. Step 3: Extrusion Granulation After the polycondensation is complete, heating is stopped, nitrogen gas is introduced into the reactor to break the vacuum and the pressure is increased to 0.2 MPa; The molten material in the reactor is conveyed to a single-screw / twin-screw extruder through a bottom melt valve. Impurities and gel particles are removed by filtration. The material is melt-extruded at an extrusion temperature of 180°C and produced into uniform particles with a particle size of 2~5mm by water-cooled stringing and rotary pelletizing. The water cooling temperature is 30℃; the pelletizing speed is 300 r / min.

[0048] Subsequently, the obtained wet particles are sent to a vacuum drying oven or a continuous vacuum dryer and vacuum dried at 70℃ and a vacuum degree ≤ -0.08 MPa for 10 h until the particle moisture content is ≤ 0.05 wt%, thus obtaining high and low temperature resistant modified PBS material.

[0049] Example 3 A high and low temperature resistant modified PBS material, comprising the following raw materials in parts by weight: Succinic acid: 100 parts; 1,4-Butanediol: 130 parts; Norbornenedimethyl-succinic acid prepolymer: 30 parts; Polyethylene glycol: 15 parts; Catalyst: 0.2 parts; Antioxidant: 0.5 parts; The number-average molecular weight of the norbornene dimethyl succinic acid prepolymer is 2000 g / mol. The number average molecular weight of polyethylene glycol is 500~2000 g / mol; The tensile strength of the high and low temperature resistant modified PBS material is 32.0 MPa, and the elongation at break is 327%. The heat distortion temperature of the high and low temperature resistant modified PBS material is 132℃; The biodegradation rate of the high and low temperature resistant modified PBS material was 92% after 6 months. The impact strength of the high and low temperature resistant modified PBS material at -20℃ is 17.2 kJ / m².

[0050] The preparation method is as follows: 1. Preparation of prepolymer: Norbornenediethanol and succinic acid were added to a reaction vessel at a molar ratio of 1:1.1 and reacted at 160℃ for 2 hours under a nitrogen atmosphere. The temperature was then lowered to 80~100℃ to obtain a prepolymer with a number average molecular weight of 2000 g / mol.

[0051] 2. Raw material ratio: 100g succinic acid, 130g butanediol, 30g prepolymer, 15g polyethylene glycol, 0.2g catalyst, 0.5g antioxidant.

[0052] 3. The preparation method is as follows: Step 1: Esterification reaction All raw materials and 0.1g of catalyst (a composite system of tetrabutyl titanate and lipase Novozym 435 in a mass ratio of 1:0.3) were added to the reactor. The reactor was purged with nitrogen three times. Under nitrogen protection, the temperature was raised to 180℃ and the esterification reaction was carried out at a stirring rate of 200 r / min for 2 hours. The water generated in the reaction was separated in real time by a distillation device until the water output reached the theoretical value of 98%, thus completing the esterification reaction. Step 2: Polycondensation reaction The remaining catalyst and antioxidant (a mixture of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1010) and tris[2,4-di-tert-butylphenyl]phosphite (antioxidant 168) in a mass ratio of 1:2) were added to the above esterification reaction system. The reaction system was heated to 230°C, and a vacuum was drawn stepwise to gradually reduce the vacuum degree of the system to 30 Pa. The vacuum polycondensation reaction was carried out at a stirring rate of 100 r / min for 3 h until the system reached the target melt viscosity, such as melt index 3-5, and the polycondensation was stopped. Step 3: Extrusion Granulation After the polycondensation is complete, heating is stopped, nitrogen gas is introduced into the reactor to break the vacuum and the pressure is increased to 0.3 MPa; The molten material in the reactor is conveyed to a single-screw / twin-screw extruder through a bottom melt valve. Impurities and gel particles are removed by filtration. The material is then melt-extruded at an extrusion temperature of 190°C and produced into uniform particles with a particle size of 2-5 mm by water-cooled stringing and rotary pelletizing.

[0053] The water cooling temperature is 40℃; the pelletizing speed is 400 r / min.

[0054] Subsequently, the obtained wet particles are sent to a vacuum drying oven or a continuous vacuum dryer and vacuum dried for 12 hours at 80°C and a vacuum degree ≤ -0.08 MPa until the particle moisture content is ≤ 0.05 wt%, thus obtaining high and low temperature resistant modified PBS material.

[0055] Comparative Example 1 No norbornenedimethyl succinic acid prepolymer and polyethylene glycol were added; the remaining raw materials and preparation process were the same as in Example 2.

[0056] Comparative Example 2 Only norbornenedimethyl succinic acid prepolymer was added, without the addition of polyethylene glycol. The other raw materials and preparation process were the same as in Example 2.

[0057] Comparative Example 3 Only polyethylene glycol was added, without norbornenedimethyl succinic acid prepolymer; the other raw materials and preparation process were the same as in Example 2.

[0058] Comparative Example 4 23.7g of PTA was used to replace the norbornenedimethyl-succinic acid prepolymer in Example 2, and the other reaction conditions were the same as in Example 2.

[0059] Comparative Example 5 13.8g of adipic acid was used to replace polyethylene glycol in Example 2, and other reaction conditions were the same as in Example 2. Comparative Example 6 23.7g of PTA and 13.8g of adipic acid were used to replace norbornenedimethylethanol-succinic acid prepolymer and polyethylene glycol in Example 2, respectively, while other reaction conditions were the same as in Example 2.

[0060] Comparative Example 7 44g of norbornenedimethyl-succinic acid prepolymer was used to replace the norbornenedimethyl-succinic acid prepolymer in Example 2, and the other reaction conditions were the same as in Example 2.

[0061] Comparative Example 8 20g of polyethylene glycol was used to replace the polyethylene glycol in Example 2, and the other reaction conditions were the same as in Example 2.

[0062] Test case Performance testing: Mechanical properties, high and low temperature performance, and biodegradability were tested on the products of Examples 1-3 and Comparative Examples 1-8. The test standards and results are shown in the table below:

[0063]

[0064] The test results show that the products of Examples 1-3 of the present invention exhibit excellent mechanical properties such as tensile strength and elongation at break. At the same time, the impact strength at -20℃ all exceed 15kJ / m², the heat distortion temperature all reach above 130℃, and the degradation rate at 6 months exceeds 90%, achieving essentially unchanged biodegradability and improved high and low temperature resistance.

[0065] Comparative Example 1 (without modified components) showed poor high and low temperature performance; Comparative Example 2 (with only prepolymer added) exhibited excellent high temperature resistance but insufficient low temperature toughness; Comparative Example 3 (with only flexible segments added) showed good low temperature toughness but no improvement in high temperature resistance; Comparative Example 4 (with the prepolymer replaced by an aromatic monomer) showed good high and low temperature performance, but the improvement in high temperature resistance was insufficient; Comparative Example 5 (with the flexible segments replaced by adipic acid) showed poor high and low temperature performance; Comparative Example 6 (with the prepolymer, flexible segments replaced by an aromatic monomer, and adipic acid) showed good low temperature toughness but no improvement in high temperature resistance; Comparative Example 7 (with 2 times the amount of prepolymer added) showed decreased high and low temperature resistance compared to Example 2; Comparative Example 8 (with 2 times the amount of flexible segments added) showed decreased high and low temperature resistance and poor high temperature resistance; none of these examples could meet the requirements for use in extreme temperature scenarios.

[0066] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A high and low temperature resistant modified PBS material, characterized in that, Including the following parts by weight of raw materials: Succinic acid: 100 parts; 1,4-Butanediol: 110~130 parts; Norbornenedimethyl-succinic acid prepolymer: 15-30 parts; Polyethylene glycol: 5-15 parts; Catalyst: 0.05~0.2 parts; Antioxidant: 0.1~0.5 parts; The number-average molecular weight of the norbornene dimethyl succinic acid prepolymer is 1000~2000 g / mol. The number-average molecular weight of the polyethylene glycol is 500~2000 g / mol.

2. The high and low temperature resistant modified PBS material according to claim 1, characterized in that, The preparation method of the norbornenediethanol-succinic acid prepolymer is as follows: norbornenediethanol (bicyclo[2.2.1]heptane-2,3-diethanol) and succinic acid are added to a reaction vessel at a molar ratio of 1:(1.05~1.1), and the reaction is carried out at a constant temperature of 140~160℃ for 2~3h under a nitrogen atmosphere, and then the temperature is lowered to 80~100℃ to obtain the prepolymer.

3. The high and low temperature resistant modified PBS material according to claim 1 or 2, characterized in that, The norbornenedimethylethanol-succinic acid prepolymer contains a rigid bicyclic cage-like cyclic aliphatic structure that can be chemically bonded into the PBS molecular chain.

4. The high and low temperature resistant modified PBS material according to claim 1 or 2, characterized in that, The lipase is selected from one or more of thermophilic lipase, lipase Novozym 435, porcine pancreatic lipase, and Candida rugosa lipase; the enzyme activity of the lipase is ≥10000 U / g.

5. A method for preparing the high and low temperature resistant modified PBS material according to any one of claims 1-4, characterized in that, Includes the following steps: Step 1: Esterification reaction Succinic acid, 1,4-butanediol, norbornenedimethyl-succinic acid prepolymer, polyethylene glycol and some catalyst are added to a reactor and esterification reaction is carried out under an inert atmosphere until the water output reaches more than 90% of the theoretical output. Step 2: Polycondensation reaction Add the remaining catalyst and antioxidant to the above esterification reaction system to carry out a polycondensation reaction; Step 3: Extrusion Granulation After terminating the polycondensation reaction, nitrogen gas is introduced to break the vacuum, and the molten material in the reaction system is extruded under pressure and granulated. After vacuum drying, a high and low temperature resistant modified PBS material is obtained.

6. The preparation method according to claim 5, characterized in that, In step 1, the reactor is heated to 160-180°C under nitrogen protection and the esterification reaction is carried out at a stirring rate of 100-200 r / min for 2-4 hours. The water generated in the reaction is separated in real time by a distillation device until the water output reaches more than 90% of the theoretical output, thus completing the esterification reaction.

7. The preparation method according to claim 6, characterized in that, In step 2, after adding catalyst and antioxidant, the reaction system is heated to 210~230℃, and at the same time, the vacuum is gradually evacuated to a vacuum degree ≤100Pa.

8. The preparation method according to claim 7, characterized in that, In step 3, the molten material in the reactor is conveyed to a single-screw / twin-screw extruder through the bottom melt valve. Impurities and gel particles are removed by filtration through a filter screen. The material is then melt-extruded at an extrusion temperature of 170~190℃ and made into uniform granules by water-cooled stringing and rotary pelletizing.

9. The preparation method according to claim 7, characterized in that, In step 3, the obtained wet particles are sent to a vacuum drying oven or a continuous vacuum dryer and vacuum dried at 60~80℃ and vacuum degree ≤-0.08 MPa for 8~12 h until the particle moisture content is ≤0.05 wt%, thus obtaining high and low temperature resistant modified PBS material.

10. An article obtained by molding and processing the high and low temperature resistant modified PBS material according to any one of claims 1-5, characterized in that, The products are cold chain packaging boxes, automotive interior parts, outdoor biodegradable tableware, or garden mulch.

Citation Information

Patent Citations

  • Preparation method for improving olybuthylenesuccinate melt strength

    CN102558793A

  • A high temperature resistant food contact fully biodegradable PBS alloy material and preparation method thereof

    CN115386199B

  • Poly (butylene adipate) copolymerized and modified poly (butylene succinate) and preparation method of poly (butylene adipate) copolymerized and modified poly (butylene succinate)

    CN115926123A

  • Heat-resistant poly (butylene succinate) copolyester and preparation method thereof

    CN118685006A